2021
DOI: 10.1111/jfbc.13749
|View full text |Cite
|
Sign up to set email alerts
|

Rat plasma protein binding of kaempferol‐3‐ O ‐rutinoside from Lu’an GuaPian tea and its anti‐inflammatory mechanism for cardiovascular protection

Abstract: Previous study found a high content of kaempferol‐3‐O‐rutinoside (KR) in Lu’an GuaPian tea, however, the rat plasma protein binding and mechanism of KR for cardiovascular protection are unclear. Thus, we studied plasma protein binding using ultrafiltration followed by UPLC, and screened its inhibition against LPS‐induced inflammation injury in vitro as well as the underlying mechanism by molecular docking and western blot. KR showed over 74% plasma protein binding ratio. Furthermore, KR may act on the toll‐lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…KR has a protective effect on the TNFhuman umbilical vein endothelial cells (HUVEC) injury model established in vitro, and its mechanism is related to its anti-inflammatory and endothelial cell protection (Yu et al, 2021). Previous research has demonstrated that KR could decrease the protein expression levels of TLR4, MyD88, and NF-κB in LPS-induced H9c2 cell injury, indicating that it inhibits inflammatory response through TLR4/MyD88/NF-κB signaling pathway (Hua et al, 2021). Our latest finding has indicated that KR could decrease IL-1β level and inhibited the expression levels of NF-κB, NLRP3, ASC, Caspase-1 p20, GSDMD, and IL-1β, suggesting that the protective effect of KR was related to regulating the NF-κB/NLRP3/Caspase-1 signaling pathway (Hua et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…KR has a protective effect on the TNFhuman umbilical vein endothelial cells (HUVEC) injury model established in vitro, and its mechanism is related to its anti-inflammatory and endothelial cell protection (Yu et al, 2021). Previous research has demonstrated that KR could decrease the protein expression levels of TLR4, MyD88, and NF-κB in LPS-induced H9c2 cell injury, indicating that it inhibits inflammatory response through TLR4/MyD88/NF-κB signaling pathway (Hua et al, 2021). Our latest finding has indicated that KR could decrease IL-1β level and inhibited the expression levels of NF-κB, NLRP3, ASC, Caspase-1 p20, GSDMD, and IL-1β, suggesting that the protective effect of KR was related to regulating the NF-κB/NLRP3/Caspase-1 signaling pathway (Hua et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In obese mice fed a HFD, TPs reduced the serum levels of TNFα, IL-1β and IL-6 by inhibiting the activation of NF- κ B ( 28 ). Lu′an GuaPian tea, which is a green tea, is rich in kaempferol-3-O-rutinoside (KR), which can protect against cardiovascular disease by inhibiting TLR4/MyD88/NF- κ B signaling and protect against myocardial injury ( 112 ). In addition, endothelial cells control vascular tone and permeability and are important for maintaining vascular homeostasis ( 113 ).…”
Section: Molecular Mechanism Of the Cardioprotective Effect Of Tpsmentioning
confidence: 99%
“…Green tea is a popular non-alcoholic beverage known for its functional effects on humans and animals with functional components, such as tea polyphenols (TPP), caffeine (Caf), and L-theanine (Thea) [11,12]. Two major mechanisms have been identified in the functional effects of green tea: (1) decreasing the absorption of lipids and proteins in the intestine, thereby reducing calorie uptake [13,14], and (2) activating AMP-activated protein kinase via TPP that is bioavailable in the liver, skeletal muscle, and adipose tissues [15].…”
Section: Introductionmentioning
confidence: 99%